Thermal conductivity enhancement of phase change materials for thermal energy storage: A review. (September 2016) - Liu, Lingkun; Su, Di; Tang, Yaojie; Fang, Guiyin
Abstract: Thermal energy storage systems have been recognized as one of the most efficient ways to enhance the energy efficiency and sustainability, and have received a growing attention in recent years. The use of phase change materials (PCMs) in building applications can not only improve the indoor thermal comfort but also enhance the energy efficiency. The necessity to enhance thermal conductivity of the PCMs is evident due to its low energy charging/discharging rates. Therefore, the high thermal conductivity additives or inserts to enhance thermal conductivity or to form the composite PCM are sought to achieve high energy charging/discharging rates. In this paper, the experimental and theoretical methods to enhance the thermal conductivity of the PCMs are summarized, and the thermal conductivity inserts/additives in recent investigations are listed and summarized. The evaluation of each thermal conductivity enhancement method is discussed.